(untitled) (Aristonothos. Rivista di Studi sul Mediterraneo Antico, 2019)
The revision of written source and Civita di Tarquinia plateau investigations results, made possible to reconstruct the settlement evolution during the Late Antiquity and Middle Ages. Until the beginning of the 6th century the presence of a civitas is confirmed. In the early Middle Ages, the presence of San Salvatore at Monte Amiata’s Abbey is underlined, especially through the dependence of Santa Restituta, investigated since 1999. The study then focuses on the structures, recognised on the Castellina plateau, of the Tarquinia’s castrum, mentioned in sources from the 14th century.